'It's a lot trickier than I expected': Assessment Issues and Dilemmas for Intern Psychologists. (31st May 2019) - Gilmore, Linda; Campbell, Marilyn
Abstract: Beyond the basic information provided in foundation texts and test manuals, there is a notable scarcity of professional literature addressing complex issues and dilemmas in assessment. At times, psychologists need to make decisions based on their professional experience or personal preferences, and it is possible that some of these decisions are made without adequate justification or reflection. Intern psychologists may be confused by the differing advice they are given by university staff, supervisors and experienced practitioners. Our aim in this project was to identify specific issues in psychoeducational assessment that need clarity, guidance and reflection, not only during postgraduate training, but also across the professional lifespan. Focus groups with educational and developmental psychology interns revealed confusion about aspects of test administration and interpretation, as well as a number of challenging professional issues. The findings have implications for trainers and supervisors, as well as for experienced practitioners.